The Strategy of Communication to Develop Tourism In Islamic Education Is Based On The Heritage of The Islamic Kingdom - Mairita, Desy; Kholil, Syukur; Khairani, Leylia (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This article aims to look at The Strategy Of Communication To Develop Tourism In Islamic Education Is Based On The Heritage Of The Islamic Kingdom. the research method used in this study uses a type of qualitative research. This research is called a qualitative research because it has been determined and produces descriptive data. This study uses a qualitative descriptive method, which is used to describe and describe scientific and engineering phenomena carried out by humans.The research was conducted at the Riau Province Tourism Office which is located at Jl. Jend. Sudirman No. 200 Pekanbaru-Riau . The key informant from the Riau Province Tourism Office was the Head of the Riau Province Tourism Office, because he was considered to know the most about the communication strategy undertaken by the Provincial Tourism Office in developing tourism based on the Islamic royal heritage. The results of this study reveal that there are various forms of tourism in Riau Province. The formulation of the strategy used is the AIDDA communication planning model (attention, interest, desire, decision, action). By using this communication planning model, communication messages directed at target audiences who are potential tourists can be directed according to the objectives of the strategy designed.